Analisis kendala pemahaman bahasa untuk mengembangkan kemampuan bernalar matematika siswa - MS, Anis Hidayati; Fauzi, Alex Haris (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Understanding of language is closely related to mathematical reasoning, because language has function as a means of communication to convey ideas or ideas to others. Submission of mathematical ideas delivered by students will show how far the level of student understading of the mathematical concepts they have. This research is a qualitative research with a descriptive approach which aims to describe the obstacles faced by students when using language on mathematical reasoning. Data obtained from observations, interviews, questionnaires, and documentations. Based on the results of the analysis conducted, it can be seen that constraints faced by students when using language on mathematical reasoning are feelings of shame and inferiority, difficulty understanding the sentence, and lack of vocabulary students have.